Protective Effect of Daikenchuto on Dextran Sulfate Sodium-Induced Colitis in Mice. (22nd January 2017) - Matsunaga, Takaharu; Hashimoto, Shinichi; Yamamoto, Naoki; Kawasato, Ryo; Shirasawa, Tomohiro; Goto, Atsushi; Fujisawa, Koichi; Takami, Taro; Okamoto, Takeshi; Nishikawa, Jun; Sakaida, Isao
Abstract : Aim . To investigate the effect of daikenchuto (TJ-100; DKT) for ulcerative colitis (UC) model mouse and assess its anti-inflammatory mechanisms. Methods . We evaluated the effects of DKT on dextran sulfate sodium- (DSS-) induced experimental colitis. First, we assessed the short-term effects of DKT using two groups: 5% DSS group and 5% DSS with DKT group. Colon length; histological scores; and interleukin- (IL-) 10, IL-1 β, and tumor necrosis factor- α mRNA expression profiles were analyzed using real-time PCR. Second, we assessed the long-term effects of DKT, by comparing survival time between 2% DSS and 2% DSS with DKT groups. Results . After 7 days, the colon lengths of DSS + DKT group were longer than those of the DSS group (mean values: 6.11 versus 5.69 cm, p < 0.05 ). Furthermore, compared to DSS group, the DSS + DKT group maintained significantly higher levels of serum hemoglobin (13.1 versus 10.7 g/dL, p < 0.05 ) and exhibited significantly higher expression levels of IL-10 (p < 0.05 ). The 2% DSS + DKT group exhibited significantly longer survival time than the 2% DSS group (70 versus 44 days, p < 0.01 ). Conclusion . Our results indicate that DKT prevented inflammation in the colon, indicating its potential as a new therapeutic agent for UC.